Pendampingan Belajar Al-Qur’an pada Anak di Desa Ladang Tuha Kecamatan Meukek Kabupaten Aceh Selatan - Mairizal, T; Anwar, Anwar; Ali, Mustafa; Nur, Muhammad; Adly, Muhammad; Safrida, Yuni; Julia, Julia; Syadza, Zaharifa; Wahida, Nur; Ara Rezkia, Putra (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2025)
Al-Qur'an education has been important in order to foster a generation that is Islamic and has noble morals. Al-Qur'an education in Aceh is not only an individual requirement but also a requirement for the implementation of Islamic law. Therefore, the STAIN Teungku Dirudeng Meulaboh community service team focuses its service activities carried out in Ladang Tuha Village, Meukek District, South Aceh Regency on assisting children in the area learning the Koran. The activity, which was held for 40 days, succeeded in improving the children's ability to read the Koran. However, due to limited time, and accompanied by other activities, assistance in learning the Al-Qur'an is optimal. For this reason, this program needs to be continued by village officials as one of the key village development programs.